2021
DOI: 10.3390/pharmaceutics13050671
|View full text |Cite
|
Sign up to set email alerts
|

Urea as a Cocrystal Former—Study of 3 Urea Based Pharmaceutical Cocrystals

Abstract: Cocrystallization is commonly used for its ability to improve the physical properties of APIs, such as solubility, bioavailability, compressibility, etc. The pharmaceutical industry is particularly interested in those cocrystals comprising a GRAS former in connection with the target API. In this work, we focus on the potential of urea as a cocrystal former, identifying three novel pharmaceutical cocrystal systems with catechin, 3-hydroxyl-2-naphthoic and ellagic acid. Interestingly, the stability of catechin u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…Interestingly, the complex formation between EA and UR was also observed in the solution, indicating its contribution to the improved solubility of EVP (EA/UR = 1/1). Fucheng et al reported EA/UR complex formation at a molar ratio of 1/2 [24]. However, in this study, EA/UR complex was formed at a molar ratio of 1/1 by solvent removal; further, the PXRD pattern of EA/UR (molar ratio = 1/2) reported by Fucheng et al differed from that of EA/UR (molar ratio = 1/1) in this study.…”
Section: Noesy Nmr Measurementcontrasting
confidence: 76%
“…Interestingly, the complex formation between EA and UR was also observed in the solution, indicating its contribution to the improved solubility of EVP (EA/UR = 1/1). Fucheng et al reported EA/UR complex formation at a molar ratio of 1/2 [24]. However, in this study, EA/UR complex was formed at a molar ratio of 1/1 by solvent removal; further, the PXRD pattern of EA/UR (molar ratio = 1/2) reported by Fucheng et al differed from that of EA/UR (molar ratio = 1/1) in this study.…”
Section: Noesy Nmr Measurementcontrasting
confidence: 76%
“… For example, it is reported that the binding of urea with polyphenols under mechanochemical conditions is predominantly through hydrogen binding, where −NH 2 of the amide binds to deprotonated catechol groups. Also, the formation of such an intermediate Ti IV –NH 2 –TA complex is likely, , in which urea can act as a catalyst to facilitate the formation of MPNs under solvent-free conditions. Furthermore, the temperature of the internal jar wall was ∼42 °C (recorded by an infrared thermometer gun).…”
Section: Resultsmentioning
confidence: 99%
“…For these purposes, different composites of urea are in use. [58][59][60][61] Furthermore, the modulation of solubility of urea derivatives is also essential as they are useful as drugs 62 and have various material properties. The release and decomposition of urea from an inorganic composite to an aqueous medium are indispensable to utilize urea and its derivatives as fertilizers.…”
Section: Introductionmentioning
confidence: 99%